Area handbook for Nigeria - Nelson, Harold D.; Mc Laughlin, James; Marvin, Babara J.; Moeller, Philip W.; Whitaker, Donald P.; American University (Washington, D.C.) (Washington : United States Government, 1972)
This volume is one of a series of handbooks prepared by Foreign Area Studies (FAS) of the American University, designed to be useful to military and other personnel who need a convenient compilation of basic facts about social, economic, political, and military institutions and practices of various countries.
"DA pam 550-157."
"One of a series of handbooks prepared by Foreign Area Studies (FAS) of the American University."
1964 ed. issued by American University, Foreign Areas Studies Division.
Includes bibliographical references and index.
rpm, 12/04/2017
Loans
Keywords: Nigeria - History; Nigeria - Social life and customs; Nigeria